Supplemental Fumigant Placement Improves Root Knot and Fusarium Wilt Management for Tomatoes Produced on a Raised-Bed Plasticulture System in Florida's Myakka Fine Sand - Land, Caroline J (Plant disease, 2022)
Fresh-market tomatoes are produced on a raised-bed plasticulture system that relies heavily on soil-applied preplant fumigants for the management of soilborne pathogens, nematodes, and weeds. Since the transition from methyl bromide to alternative fumigants, growers have experienced a resurgence of several soilborne pests and pathogens, including root-knot nematode caused by Meloidogyne spp. and Fusarium wilt caused by Fusarium oxysporum f. sp. lycopersici race 3. This resurgence is attributed to the inability of the alternative fumigants to effectively disperse through the soil in the same manner as methyl bromide. Two supplemental fumigation strategies, the application of chloropicrin (PIC) below bed edges (herein "supplemental PIC") and broadcast deep-shank applications of 1,3-dichloropropene (1,3-D), were evaluated in conjunction with standard raised-bed applications of Pic-Clor 60, Pic-Clor 80, and Pic 100 covered with a virtually impermeable film or a totally impermeable film. Large-plot replicated studies were conducted in two separate commercial tomato fields with a history of production losses caused by root-knot nematode and Fusarium wilt. Deep-shank 1,3-D applications significantly reduced the recovery of root-knot and total parasitic nematodes across field sites before the preparation of raised beds. Both supplemental PIC and deep-shank 1,3-D reduced root-knot galling and Fusarium wilt incidence, but the latter supplemental treatment statistically had the greatest impact. Fumigant applied within raised beds or plastic film had no significant effect on root-knot galling or Fusarium wilt. Although both supplemental fumigation strategies had a significant effect on pest and disease pressure, neither statistically improved tomato yields based on small subplot harvests. Controlled laboratory experiments confirmed the fungicidal activity of 1,3-D against F. oxysporum f. sp. lycopersici, with 75, 90, 95, and 99% lethal doses corresponding to estimated field application rates of 56.1, 93.5, 121.6, and 184.7 liters/ha, respectively. The results demonstrate how fumigant placement can improve pest and disease control activity with current fumigant alternatives to methyl bromide and further support the broader pesticidal activity of some chemical fumigants